Spastic dysphoni - Shyamala Dharmaraj (Journal of All India Institute of Speech and Hearing, 1971)
The following case was seen at the All India Institute of Speech and Hearing and is being presented to suggest and support a point of view about treatment that may be beneficial to some such cases.